2020
DOI: 10.3389/fonc.2020.00543
|View full text |Cite
|
Sign up to set email alerts
|

Texture Analysis of Breast DCE-MRI Based on Intratumoral Subregions for Predicting HER2 2+ Status

Abstract: Background: Breast tumor heterogeneity is related to risk factors that lead to aggressive tumor growth; however, such heterogeneity has not been thoroughly investigated.Purpose: To evaluate the performance of texture features extracted from heterogeneity subregions on subtraction MRI images for identifying human epidermal growth factor receptor 2 (HER2) 2+ status of breast cancers.Materials and Methods: Seventy-six patients with HER2 2+ breast cancer who underwent dynamic contrast-enhanced magnetic resonance i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 62 publications
1
16
0
Order By: Relevance
“…This is consistent with previous findings. 38,39 The results indicate that the 3D tumor subregion related to FFK is closely associated with tumor growth and angiogenesis, 25 and thus can demonstrate better diagnostic performance for molecular subtypes, Ki-67, and tumor grade. Our results also showed lower diagnostic performance for the basal-like subtype than that of the other subtypes.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…This is consistent with previous findings. 38,39 The results indicate that the 3D tumor subregion related to FFK is closely associated with tumor growth and angiogenesis, 25 and thus can demonstrate better diagnostic performance for molecular subtypes, Ki-67, and tumor grade. Our results also showed lower diagnostic performance for the basal-like subtype than that of the other subtypes.…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies, which focused on the whole tumor, have identified imaging biomarkers associated with histological characteristics 34–36 . Radiomic analysis based on intra‐tumoral regions showed that features from the subregions were closely associated with histological characteristics than those based on the whole tumor 25,37,38 . Different from these analyses of intra‐tumoral heterogeneity, this study investigated PK heterogeneity within tumor for enhancing the prediction of molecular subtypes, Ki‐67, and tumor grade.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the course of the last 5-10 years, TA has been increasingly become a tool for maximizing the amount of information extracted from virtually any medical imaging modality [12][13][14]. Least absolute shrinkage and selection operator (LASSO) [15], logistic regression analysis (LRA) [16], and support vector machine (SVM) [17] have become very popular machine learning tools for analyzing complex data that often arise in radiological research. LASSO is a novel feature selection method that can use a penalty function to filter data with a large number of covariates [18][19].…”
Section: Introductionmentioning
confidence: 99%